Analysis And Design Of Website-Based Swimming Course Information System At Jatayu Swimming Club - Ni Luh Suminiasih; Suryawan, Komang Ada Gelgel; Ni Made Estiyanti; I Nyoman Yudi Anggara (Innovative: Journal Of Social Science Research, 2023)
Jatayu Swimming Club is a non-formal educational institution that provides swimming courses. Jatayu Swimming Club's operational activities still use a manual system, from new member registration, transaction processing, and scheduling to reporting. An information system is needed to improve services so that services are more effective and efficient. The research method used is the system development method, namely the Prototype Method. The design of the swimming course information system is based on a needs analysis by conducting interviews, observations, and literature studies to reduce the difficulties that occur in operational services at the Jatayu Swimming Club. This study only focuses on three stages: gathering needs, building prototyping, and prototyping evaluation. The swimming course information system design process at Jatayu Swimming Club uses system modeling, including Context Diagrams, Data Flow Diagrams, and Entity Relationship Diagrams, and produces a User Interface. It is hoped that with the design of this system, Jatayu Swimming Club can apply it to become an information system that can be run for company operations.